Monoclonal antibodies to detect human tumours: an experimental approach. Issue 3 (March 1981) - Moshakis, V; McIlhinney, R; Raghavan, D; Neville, A M
Abstract : The use of monoclonal antibodies which can be raised to antigens of choice offers a selective and specific approach for the detection of tumours both in vivo and at a cellular level in biopsy specimens. We demonstrate that a monoclonal antibody raised to human teratoma will localise in a teratoma, growing as a xenograft in immune-suppressed mice.